Indian evidence act, 1872 (1 of 1872) - Shree ram law house; Bare Act (Chandigarh Shree ram law house)
Indian evidence act, 1872 (1 of 1872) as amended by the Jammu and Kashmir reorganisation act, 2019.
Keywords: Indian Evidence Act